The Influence of the Nagori-Owned Business Agency (BUMNag) Bah Lias on Community Income in Bah Lias Village, Kec. Bandar, Simalungun District - Elidawaty Purba; Darwin Darwin; Taufik Parinduri (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The village economy can increase if the income of the village community can increase, one of the efforts made by the order to increase the income of the rural community is through the Village Owned Enterprise or BUNDES. Nagori Bah Lias is one of the villages that has a village-owned enterprise called BUMNag BAH LIAS, the existence of BUMNAG Bah Lias has improved the economy of Nagori Bah Lias. Through BUMNAG Bah lias, 5 business units have been formed., from the The questionnaire was taken from 30 respondents, then analyzed using regression analysis, the contribution was still relatively small because the business unit was also still on a small scale. The results of the regression analysis show that the effect of BUMNag Bah Lias on ime is only 10.4% if there is an additional unit of labor. Based on the relationship between labor and opinion, it still shows low results, namely only 0.1 because the number of workers in BUMNag Bah Lias is relatively small and based on the coefficient of determination it is found that the effect of labor on BUMNaG Bah Lias is only 1%. From the research results it is suggested that the government invest in the potential of the village to add to other business units and, to socialize to the community the benefits of BUMNag. Thus, it is hoped that the presence of BUMNag Bah Lias will advance the economy of Nagori Bah Lias.